Corrigendum: Statistical tests in particle physics - Valenzuela, Mississippi (2025)
In developing equation (21) and not listing it in the recent paper [1], an inadvertent error caused the rest of the numerical expressions  to not be listen in the proper order. The main results and conclusions of the paper reamin unchanged.